SHORT INVESTIGATIVE RESEARCH ON LEARNING DIFFICULTIES IN PRIMARY SCHOOL YEARS - Florentin Remus MOGONEA (Universitaria Publishing House, Craiova, 2022)
In accordance with the efforts of the education systems around the world, the Romanian one also strives to create and implement a set of projects that include a generous, comprehensive educational offer, in order to meet the growing and diverse educational needs of a population with increasing and diverse educational necessities. This is how inclusive or integrated pedagogy (education) appeared, as well as the pedagogy of gifted children (the pedagogy of elitism) or the educational alternatives (Waldorf, Montessori, Freinet, Step by Step). With all these efforts to meet the educational needs of a mosaic and constantly changing population, one category of individuals has not been researched and explored enough: it is the category of children with learning difficulties. Research on this category of children has been carried on mainly during the last four decades. The present study aims to address the issue of learning difficulties at the level of primary education, from the perspective of an ameliorative type of research, which proposes a series of effective action methods to reduce the learning difficulties in the Romanian language registered by the students of some classes in the primary school years. These methods can obviously be extended and adapted to other classes and other school subjects.